Alterations in the Adaptation of Pancreatic Enzymes to Food Quality under the Influence of Hexachlorocyclohexane and Tetramethylthiuram Disulfide - Babadjanova F.A.; Askaryants V.P; Yunusov A.A. (Academia Open, 2026)
General Background: The pancreas demonstrates adaptive capacity to modify enzymatic secretion in response to dietary composition, a mechanism essential for efficient nutrient hydrolysis and metabolic homeostasis. Specific Background: Organochlorine pesticides, particularly hexachlorocyclohexane (HCH) and tetramethylthiuram disulfide (TMTD), have been associated with digestive system disorders, yet their effects on pancreatic enzymatic adaptation and intestinal enzyme-forming function remain inadequately characterized. Knowledge Gap: The extent to which chronic pesticide exposure disrupts the pancreas's ability to adapt enzyme secretion to qualitative changes in food composition, and how these compounds affect small intestinal hydrolytic capacity, has not been systematically investigated. Aims: This study examined the effects of chronic HCH (1/20 LD₅₀ for 30 days) and TMTD (1/20 LD₅₀ for 60 days) exposure on pancreatic enzymatic adaptation to protein-rich and fat-rich dietary stimuli in rats, alongside assessment of small intestinal enzyme-forming function. Results: Control animals exhibited adaptive increases in protease activity following protein intake and lipase activity following fat intake within intestinal chyme; HCH exposure delayed these adaptive responses, whereas TMTD completely abolished pancreatic enzymatic adaptation to food quality, with both pesticides significantly suppressing intestinal enzyme activities. Novelty: This investigation provides the first systematic evidence that organochlorine pesticides disrupt both pancreatic adaptive mechanisms and intestinal hydrolytic enzyme function in a dose-dependent and time-dependent manner. Implications: These findings indicate that pesticide exposure compromises digestive efficiency through dual mechanisms affecting pancreatic regulation and intestinal enzymatic capacity, potentially contributing to metabolic dysfunction in exposed populations.Keyowrds : Pancreatic Enzyme Adaptation, Hexachlorocyclohexane Toxicity, Tetramethylthiuram Disulfide, Intestinal Enzyme Function, Organochlorine Pesticide EffectsHighlight : Chronic HCH exposure delays pancreatic adaptive response to dietary protein and fat stimuli. TMTD completely abolishes enzymatic adaptation mechanisms in exocrine pancreatic secretion regulation. Organochlorine pesticides suppress intestinal enzyme activity while paradoxically increasing mucosal amylase levels.